ANALISIS TINGKAT PENDAPATAN NELAYAN PADA PENANGKAPAN IKAN NIKE (Awaous melanocephalus) DI DESA KARYA MURNI KECAMATAN PAGUYAMAN KABUPATEN BOALEMO - Erlansyah Erlansyah; Abdurahman Mohamad Kano; Tri Zulfikri (Universitas Muhammadiyah Gresik, 2024)
This study aims to determine about income analysis fishermen's income when catching Nike fish (Awaous melanocephalus) in Karya Murni Village, Paguyaman District, Boalemo Regency. The research method are interview and direct observation which was analyzed descriptive quantitative. In addition, this research indicated that the total costs incurred by Nike fish fishermen in catching Nike fish are IDR 5.220.500, while the total income of Nike fish fishermen are IDR 7,000,000, and the profit obtained from catching Nike fish are IDR 1.779.500. Return Cost Ratio (RCR) from the Nike fishing was 1.34 (R/C>1), so this business is worth to develop. However, at the Break Effect Point (BEP) production was 149 kg, it was mean that fishermen had to produce 149 kg of Nike fish achieved from individual respondents of Nike fish fishermen in order to occur the BEP. Meanwhile, the Break Effect Point (BEP) price achieved was IDR 26.103, which means that Nike fish fishermen must get a profit of more than IDR 26.103 to return on investment.